THE PROBLEM OF EXPORTS AND IMPORTS IN AFRICAN COUNTRIES - Chileshe, Jonathan (Dirasat in Economics and Business, 1972)
Accompanying statistical tables only reflect in part the extent to which world trade has expanded in recent years. To a very large extent, most of these tables deal with volume and values or rates of exports and imports. Some more tables could have been compiled to show the direction and flow of trade for particular trade areas as well as by commodity groups. At no time must sight be lost of certain salient features when it comes to interpreting export and import data of the trade of develop ing African countries which have a rather high incidence of inavailabi lity of correct data at any particular point in time. An additional factor to be borne in mind concerning export and import data is that they merely reflect recorded past performances. Hence they cannot be presumed as a true economic barometer in understanding some of the economic maladies of the countries or the region in general. These limitations apart, it is still possible that export and import figures could provide working basis for the formulation of sound commercial policy being designed for economic development ; secondly, they could provide a means for working out projeceted trade and development targets ; and are useful as a basis for comparison of economic performance in international trade etc.